Eksistensi Bentor terhadap Aktivitas Wisata di Pulau Maitara Kota Tidore Kepulauan - Zulkifli Lante; Dewi Apriani Aco; Safrudin Amin (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research aims to determine the existence of bentors and visitors views regarding the presence of bentors on tourist activities on Maitara Island, Tidore Islands City. This type of research is descriptive qualitative. Data collection was carried out by means of observation and interviews. Maitara Island was chosen as the research location because there are people who use bentor as a means of transportation to support activities at tourist attractions. The results of this research found that: 1) Bentor makes a big contribution in helping and carrying out activities at tourist attractions, but there is no contribution to income for the village government, 2) With Bentor, it can also make it easier for visitors who come on holiday to move from one tourist attraction. from one village to another village's tourist attraction considering that the distance is quite far if traveled on foot, 3) The visitors view of the bentor on Maitara Island makes them feel happy because apart from being able to make things easier for them, bentor is also one of the unique and new things in a tourist attraction and Bentor also provides song services so that visitors can experience the journey with enjoyment when touring Maitara Island with Bentor.